Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Membentuk Dengan Berbagai Media Pada Anak TK Al-Madani - Winda Oktaviana; Rizki Gusmanto (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Based on the results of observations, the children of TK Al-Madani still encounter obstacles in their fine motor skills, including children preferring to play outside rather than taking part in activities that involve the coordination of their fingers so that children often do not complete activities, lack activities that stimulate the teacher's fine motor skills and the media used is less varied. From the teacher's observations, there were 2 children who could, 6 children who could not and 4 children who could not do activities that involved fine motor skills. The aim of this research is to determine the increase in fine motor skills through shaping activities with various media in children at TK Al-Madani. This research was conducted using the classroom action research method. Classroom action research is research carried out in social situations carried out by researchers in the form of reflective and collective research in order to improve their social practice reasoning. Experts explain that this classroom action research has four stages, namely planning, implementation, observation and reflection. The results of the research show that fine motor skills in TK Al-Madani children can be improved through montage activities. From data on shaping activities using various media in Cycle I, it was found that 6 children or 30% of the total children in the class received BSB criteria, while 14 other children received BSH criteria. The average score obtained by children was 74.1. Meanwhile, from the Cycle II data, it was found that 17 children or 85% of the total children in the class received BSB criteria, while 3 other children received BSH criteria. The average score obtained by children was 74.1. Keywords: Fine Motor, Forming Activities, Various Media